A comparison of methods to assess cell mechanical properties - Wu, Pei-Hsun; Aroush, Dikla Raz-Ben; Asnacios, Atef; Chen, Wei-Chiang; Dokukin, Maxim E.; Doss, Bryant L.; Durand-Smet, Pauline; Ekpenyong, Andrew; Guck, Jochen; Guz, Nataliia V.; Janmey, Paul A.; Lee, Jerry S. H.; et al. (Nature Methods, 2018)
The mechanical properties of cells influence their cellular and subcellular functions, including cell adhesion, migration, polarization, and differentiation, as well as organelle organization and trafficking inside the cytoplasm. Yet reported values of cell stiffness and viscosity vary substantially, which suggests differences in how the results of different methods are obtained or analyzed by different groups. To address this issue and illustrate the complementarity of certain approaches, here we present, analyze, and critically compare measurements obtained by means of some of the most widely used methods for cell mechanics: atomic force microscopy, magnetic twisting cytometry, particle-tracking microrheology, parallel-plate rheom-etry, cell monolayer rheology, and optical stretching. These measurements highlight how elastic and viscous moduli of MCF-7 breast cancer cells can vary 1,000-fold and 100-fold, respectively. We discuss the sources of these variations, including the level of applied mechanical stress, the rate of deformation, the geometry of the probe, the location probed in the cell, and the extracellular microenvironment.
CRIS-Team Scopus Importer:2022-08-05